2002
DOI: 10.1053/jlts.2002.33967
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine gene polymorphisms and acute human liver graft rejection

Abstract: Interindividual differences exist in the capacity to produce cytokines. It has been reported that levels of in vitro cytokine production measured after stimulated cell culture are associated with polymorphisms in cytokine genes. Moreover, a correlation between heart, kidney, liver, and lung graft rejection or survival with cytokine gene polymorphisms has been described. In the present study, we analyzed the association of gene polymorphisms in T helper subtype 1 (T H 1-), T H 2-, and regulatory-type cytokines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 62 publications
4
21
0
Order By: Relevance
“…33 In liver transplant recipients, the TNF-a high genotype was associated with acute rejection in some studies [51][52][53] but not in others. [54][55][56] The TNF-a high genotype correlates with acute rejection in multiple adult kidney transplant studies from various demographic populations. 23,[45][46][47]57 Interleukin-6.…”
Section: Interleukinmentioning
confidence: 99%
“…33 In liver transplant recipients, the TNF-a high genotype was associated with acute rejection in some studies [51][52][53] but not in others. [54][55][56] The TNF-a high genotype correlates with acute rejection in multiple adult kidney transplant studies from various demographic populations. 23,[45][46][47]57 Interleukin-6.…”
Section: Interleukinmentioning
confidence: 99%
“…For example, the tumor necrosis factor (TNF)-A-308 polymorphism was found to be associated with severe rejection after heart, kidney, and liver transplantation'-4 and with a wide variety of diseases, such as primary sclerosing cholangitis,5,6 autoimmune hepatitis,GJ cerebral malaria,s mucocutaneous leishmaniasis,g and asthma.10 These associations were not always confirmed; for example, some studies could not show a relationship between the TNF-A-308 gene polymorphism and liver graft rejection. [11][12][13] The reasoning behind the proposed involvement of cytokine gene polymorphisms in diseases or disease manifestations is that they may influence in vivo cytokine levels. This presumption is based on the observation that individuals differ with respect to the level of cytokine production after in vitro culture of their cells and that these differences may be attributed partly to single-nucleotide or microsatellite polymorphisms of their cytokine genes.…”
mentioning
confidence: 99%
“…This study investigated whether a genetic predisposition involving polymorphisms of TH1-, TH2-, or regulatory-type cytokine genes was associated with rejection following human liver transplantation. Several polymorphisms in cytokine genes have been investigated for their possible relationship with cytokine production (Platz et al, 1996;Warlé et al, 2002;Shi et al, 2008;Liu et al, 2009;Zhang and Sun, 2010;Rattanasiri et al, 2013) and graft rejection. Polymorphisms of IL10, TNF, and TGFB1 have been reported to be closely linked to AR (Bathgate et al, 2000;Jonsson et al, 2001;Mas et al, 2004;Azarpira et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have shown an effect on rejection (Warlé et al, 2002;Rattanasiri et al, 2013), others have shown no association (Conti et al, 1998;Xie et al, 2008). The regulatory-type cytokines, such as transforming growth factor-b1 (TGF-b1), may influence both TH1-and TH2-type cytokines in the immune response (Liu et al, 2009), and some researchers have reported that they are upregulated in rejection (Eikmans et al, 2002), while others have reported no relationship (Eurich et al, 2011;Rattanasiri et al, 2013).…”
Section: Introductionmentioning
confidence: 99%